2019
DOI: 10.15388/omee.2019.10.00003
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Human Capital on the Relationship Between Strategic Innovation and the Performance of Manufacturing SMEs in Yemen

Abstract: The purpose of this paper is to fill gaps in the human capital literature, first, by providing insights into the relationship between human capital and strategic innovation and the performance of Small and Medium Enterprises (SMEs), and second, by exploring the role of human capital as a mediating variable. Although SMEs perform a vital role in the economic development of countries worldwide, developing countries tend to lag behind developed countries in this sector; hence, there is a need to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 73 publications
(91 reference statements)
3
17
0
Order By: Relevance
“…In addition to the direct relationship between talent management and performance, Alqershi et al (2019) emphasized that scholars have shown an interest in the mediating role of human capital (Rezaei et al, 2021;Subramony et al, 2018;Nieves and Quintana, 2018). We provide confirmatory evidence for the mediating effect of human capital in the relationship between TMM and SBP, which means that H6 is supported.…”
Section: Effect Of Talent Managementsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition to the direct relationship between talent management and performance, Alqershi et al (2019) emphasized that scholars have shown an interest in the mediating role of human capital (Rezaei et al, 2021;Subramony et al, 2018;Nieves and Quintana, 2018). We provide confirmatory evidence for the mediating effect of human capital in the relationship between TMM and SBP, which means that H6 is supported.…”
Section: Effect Of Talent Managementsupporting
confidence: 62%
“…They reported significantly positive direct effects between HC on both variables. Additionally, by using the philosophy to justify its mediating role in the relationship between TM and SBP, Alqershi et al (2019) and Raineri (2017) recommended that HC can contribute to sustainable performance.…”
Section: Human Capitalmentioning
confidence: 99%
“…This allows obtaining a global vision of the influence of the structural capital of the SME on innovation. Previous studies conducted in different countries and focused on SMEs have only partially addressed some of the components of structural capital (Santos-Rodriguez and Figueroa-Dorrego, 2011; Hogan and Coote, 2014; Ariawan et al , 2016; Agostini and Nosella, 2017; Dedahanov et al , 2017; Allameh, 2018; Alazawi et al , 2018; Kahan, 2019; Alqershi et al , 2019). Additionally, structural capital is studied in the context of an emerging country.…”
Section: Introductionmentioning
confidence: 99%
“…The severe competition reduced the contribution of manufacturing industry to Yemeni Gross Domestic Product from 24% in 2010 to only 6.4% in 2015. In addition to the competition, manufacturing industry contribution was deteriorated due to their insufficient experience, inappropriate business environment, poor incentives, poor infrastructure, lack of employee training, and, as a result, lack of skilled human capital [5]. The new competition trend has created a lot of problems for the manufacturing industry in many developing countries such as Yemen [6].…”
Section: Introductionmentioning
confidence: 99%